ENHANCING SELF-CONFIDENCE IN ENGLISH COMMUNICATION AMONG TOURISM ACADEMY STUDENTS USING ERROR-FRIENDLY ENVIRONMENT METHOD: A QUALITATIVE STUDY - Prasetyo, Sigit (Journal of Innovation Research and Knowledge, 2024)
This qualitative study investigates the impact of an error-friendly environment on enhancing self-confidence in English communication among students at a Tourism Academy. The study addresses the challenge faced by students in achieving fluency and confidence in English, crucial for their future careers in hospitality and tourism. The research aims to explore how creating a supportive and non-judgmental classroom atmosphere contributes to students' willingness to engage in English communication. Through thematic analysis of interviews and observations, key themes related to self-confidence, error management, and communicative competence were identified. The findings reveal that an error-friendly environment significantly boosts students' confidence, leading to improved language skills and a more positive learning experience. The study concludes with practical recommendations for educators to integrate error-friendly practices into their teaching methods.